Design of Feeding System in Recycle Vending Machine (RVM) - ABDUL SHUKOR, NUR NABILAH HUDA; Abdul Rahim, Abdul Khalil (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A recycling machine, also called a "reverse vending machine," is a machine that accepts used or empty glass bottles, plastic bottles, or aluminium in exchange for a reward. After recycling materials are inserted, they are compressed, sorted, and evaluated. After the object has been scanned and confirmed, it is crushed and placed in the appropriate storage area for classified materials. The machine provides incentives, such as cash or coupons, after processing the item. This project's purpose is to provide a comprehensive feeding system for receiving and sorting recyclables in a recycle vending machine (RVM). This project used George E Dieter design process for design this machine. The design process consists of eight phase which are Define problem, Gather information, Concept generation, Concept evaluation, Product architecture, Configuration design, Parametric design and Detail design. The existing patent and available machine were referred to generate idea for the banana slicing machine. The selected idea and concept then will be modelled using Solidwork Software. Solidwork Software also being used to conduct some engineering analysis. The author also making analysis using theoretical calculation. The result of the analysis shows that the machine can feed 5s per unit. The overall dimension of the Feeding system is 1522mm x 806mm x 350mm with the weight of 26.64 kilogram.